2003
DOI: 10.1007/bf03345139
|View full text |Cite
|
Sign up to set email alerts
|

Three-hour spontaneous GH secretion profile is as reliable as oral glucose tolerance test for the diagnosis of acromegaly

Abstract: The diagnosis of acromegaly, in an appropriate clinical context, usually relies on lack of GH suppression below 1 microg/l during OGTT coupled with elevated IGF-I levels. On the other hand, in normal subjects glucose-induced inhibition of GH secretory bursts without any further decrease of interpulse GH levels had already been shown. Based on the foregoing, we aimed to compare the diagnostic reliability of OGTT-induced GH nadir with that recorded during 3-h spontaneous GH secretion. In 59 acromegalic patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 32 publications
0
16
0
2
Order By: Relevance
“…In studies in which gender was taken into account [13,14], the upper normal limit of the GH nadir during the OGTT ranged between 0.057 and 0.25 lg/l in males and was 0.71 lg/l in females; note that the Immulite 2000 method gave two-fold higher concentrations than the Autodelfia method [14] in this range of GH values. Grottoli et al using a less sensitive method (detection limit 0.15 lg/l), found that the upper normal limit of the GH nadir during the OGTT was 0.7 lg/l, irrespective of gender [21,22]. In the oldest study included in Table 2 [23], based on an EIA, the GH level in one of the 37 healthy subjects remained above 1 lg/l after a glucose load.…”
Section: Dynamic Tests For Diagnosis Of Acromegalymentioning
confidence: 96%
“…In studies in which gender was taken into account [13,14], the upper normal limit of the GH nadir during the OGTT ranged between 0.057 and 0.25 lg/l in males and was 0.71 lg/l in females; note that the Immulite 2000 method gave two-fold higher concentrations than the Autodelfia method [14] in this range of GH values. Grottoli et al using a less sensitive method (detection limit 0.15 lg/l), found that the upper normal limit of the GH nadir during the OGTT was 0.7 lg/l, irrespective of gender [21,22]. In the oldest study included in Table 2 [23], based on an EIA, the GH level in one of the 37 healthy subjects remained above 1 lg/l after a glucose load.…”
Section: Dynamic Tests For Diagnosis Of Acromegalymentioning
confidence: 96%
“…Since overt diabetes mellitus may limit the feasibility or reliability of the oral glucose-tolerance test for GH suppression, alternative testing such as thyrotrophin-releasing hormone stimulation may be indicated. There is also recent evidence than a 3-h GH profile may give results similar to oral glucose-tolerance test in acromegalics (33).…”
Section: Peculiarity Of Bioclinical Endocrine Changes In the Elderlymentioning
confidence: 97%
“…Of note, some authors have shown that the nadir GH levels obtained following glucose intake are not specific to glucose and also occur after water ingestion or even spontaneous GH measures. They showed that glucose rather inhibits spontaneous GH surges [17, 18]. The exact molecular mechanisms by which glucose modulates GH release are yet to be determined.…”
Section: Gh Response To Oral Glucose and To Chronic Hyperglycemiamentioning
confidence: 99%